Teaching courses online: A review of the research - Tallent-Runnels, Mary K; Thomas, Julie A; Lan, William Y (Review of educational research, 2006)
This literature review summarizes research on online teaching and learning. It is organized into four topics: course environment, learners' outcomes, learners' characteristics, and institutional and administrative factors. The authors found little consistency of terminology, discovered some conclusive guidelines, and identified developing lines of inquiry. The conclusions overall suggests that most of the studies reviewed were descriptive and exploratory, that most online students are nontraditional and Anglo American, and that few universities have written policies, guidelines, or technical support for faculty members or students. Asynchronous communication seemed to facilitate in-depth communication (but not more than in traditional classes), students liked to move at their own pace. Learning outcomes appeared to be the same as in traditional courses, and students with prior training in computers were more satisfied with online courses. Continued research is needed to inform learner outcomes, learner characteristics, course environment, and institutional factors related to delivery system variables in order to test learning theories and teaching models inherent in course design. (DIPF/Orig.).